Rigidity of square grids with holes - Gáspár, Zsolt; Radics, Norbert; Recski, Andras (Computer Assisted Methods in Engineering and Science, 2023)
Bolker and Crapo gave a graph theoretical model of square grid frameworks with diagonal rods of certain squares. Using this model there are very fast methods for connected planar square grid frameworks to determine their (infinitesimal) rigidity when we can use diagonal rods, diagonal cables or struts, long rods, long cables or struts. But what about square grids containing some kind of holes? We will show that the model can be extended to the problem of holes too.